Investigation on the solidification mechanism and mechanical properties of basalt dust waste in soil subgrade construction - Jun, Li; Yilin, Wu; Ya, Ma; Chuanshan, Wu; Wei, Lu (Frontiers in Earth Science, 2025)
In order to solve the problems of soil scarcity, and the properties of structural loose, poor grading, and poor cohesion of loess in the Huang River area during the construction of the Jibin intercity railway project, to improve the ecological and environmental benefits of the Jibin railway project, and to reduce cement consumption, this article first relies on engineering research to recycle waste stone powder from surrounding stone processing plants, and powder activation and particle size optimization based on self-developed processing system are conducted; Secondly, collect loess soil samples from the Huang River area, conduct soil sample screening and compaction tests, and obtain the particle size distribution and optimal moisture content of the loess; Introducing slag to regulate the activity of stone powder, based on the principle of alkali activation, the orthogonal experimental design method was used to study and compare the influence of alkali activator type, content, and silicon sodium content on the mechanical properties of cementitious materials prepared from basalt rock powder. The variance analysis method was used for parameter sensitivity analysis; Once again, based on the optimal mix ratio determined by the above-mentioned stimulation test and the optimal moisture content and maximum dry density obtained from the compaction test, 7-day unconfined compressive strength tests (20%, 18%, 16%, 14%, 12%, and 10%) were conducted on the silt at different dosages to determine the optimal mixing ratio of the stone powder solidification material. The research results show that the maximum dry density of loess in the Huang River area is 1.84 g/cm3, and the optimal moisture content is 15.8%; As the proportion of sodium hydroxide and sodium silicate increases, the mechanical strength of the stone powder cured material shows a trend of first decreasing and then increasing, while as the proportion of slag powder decreases, its strength significantly decreases; Micro tests show that with the increase of the amount of stone powder curing materials, a large number of gel materials and ettringite are generated in the improved silt, forming a cementitious space network structure, improving the structural integrity and strength; The on-site test results show that the stone powder improved loess in the yellowing area can meet the requirements of roadbed filling, and the cost is reduced by 51% compared to the cement solidification method. This study provides an economical and environmentally friendly roadbed filling solidification technology for the Jibin high-speed railway and similar projects, which can provide experimental results and on-site application references for related engineering construction.